Implementasi Model Teams Games Tournament untuk Meningkatkan Kemampuan Numerasi Siswa Sekolah Dasar - Rani Ayunda; Riduan Febriandi (Jurnal Elementaria Edukasia, 2023)
Numeracy has an important role in helping students to be able to solve problems that can be encountered in the surrounding environment. This research is Classroom Action Research (PTK) aimed at improving students' numeracy skills through the application of the Teams Games Tournament (TGT) model in mathematics subjects. This research method is Classroom Action Research (PTK) which is carried out in 2 cycles consisting of 4 stages, namely planning, implementation, observation and reflection. The subject of this research was class V at SDN 34 Lubuklinggau with a total of 19 students. Data collection techniques are observation, interviews, and tests. Data analysis techniques use average score or percentage techniques. The results of this research show that the application of the Team Games Tournament (TGT) model can improve the mathematical numeracy skills of class V students at SDN 34 Lubuklinggau. The average percentage of students' numeracy abilities in the pre-cycle was 21.1% in the first cycle to 47.4%, then in the second cycle it increased to 68.42%. This research concludes that the application of the Teams Games Tournament (TGT) model can improve the mathematical numeracy skills of class V students at SDN 34 Lubuklinggau in mathematics lessons.